2004
DOI: 10.1007/s00221-004-1859-4
|View full text |Cite
|
Sign up to set email alerts
|

Finger coordination during moment production on a mechanically fixed object

Abstract: The moment production by several fingers on a mechanically fixed vertically oriented handle was studied under the systematic variations of task parameters such as (a) moment magnitude (1.0 Nm and 2.0 Nm) and (b) direction of moment production (into pronation and supination), as well as (c) vertical position of the handle from the moment axis, P (0, 2.0, 4.0, and 6.0 cm in both directions). The purpose of this study was twofold: to investigate the dependences between the task parameters and the performance vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…In particular, Salter and Darcus (1952) report higher peak pronation torque magnitudes at some elbow flexion angles but not at others. A more recent study (Shim et al 2004b) reported somewhat higher torque magnitudes during supination efforts. To our knowledge, no study compared indices of variability in torque production tasks into pronation and supination.…”
Section: Moment Of Force Of Its Variabilitymentioning
confidence: 86%
See 1 more Smart Citation
“…In particular, Salter and Darcus (1952) report higher peak pronation torque magnitudes at some elbow flexion angles but not at others. A more recent study (Shim et al 2004b) reported somewhat higher torque magnitudes during supination efforts. To our knowledge, no study compared indices of variability in torque production tasks into pronation and supination.…”
Section: Moment Of Force Of Its Variabilitymentioning
confidence: 86%
“…Shim et al 2004b), and involvement of the thumb (Olatsdottir et al 2005). We would like to note, however, that at least one study reported high indices of moment-stabilizing synergies during more natural grasping tasks (Shim et al 2004a).…”
Section: Concluding Commentsmentioning
confidence: 97%
“…Earlier studies have suggested the mechanical advantage hypothesis (Buchanan et al 1989;Prilutsky 2000;Zatsiorsky et al 2002;Shim et al 2004a), which states that effectors (muscles or digits) with longer lever arms contribute more to the total rotational action as compared to effectors with shorter lever arms. In our study, two fingers (I and M) produced PR moments (M PR ) while two other fingers (R and L) produced SU moments (M SU ).…”
Section: Moment Production By Individual Fingersmentioning
confidence: 99%
“…Only a handful of studies explicitly addressed the rotational action by the hand (e.g., Johansson et al 1999;Latash et al 2004). In particular, studies of finger force co-variation across static tasks withholding an object have suggested that the control of the hand action can be represented as a superposition of two processes, the control of the gripping action and the control of the rotational action (Shim et al 2003(Shim et al , 2004a). As such, hand control seems to obey the principle of superposition introduced in robotics (Arimoto et al 2000(Arimoto et al , 2001; according to this principle, some complex tasks performed by a set of effectors may be more efficiently controlled if they are decomposed into sub-tasks that have their own controllers with no interference with each other.…”
Section: Multi-finger Synergies Stabilizing Rotational Hand Actionmentioning
confidence: 99%
“…In particular, manipulative tasks have been investigated in order to understand this inherent trait of the neuromotor system [4][5][6][7][8] . Because of its singular mechanical structure, the hand stands out as a "convenient" tool in the study of the problem of motor redundancy 9 .…”
Section: Introductionmentioning
confidence: 99%